Physical and motor development of the students enrolled at the University of Warmia & Mazury in Olsztyn, Poland, in relation to their financial and urbanization status - Robert Podstawski; Krzysztof Boryslawski; Renata Urbanska-Gizinska (Physical Education of Students)
Purpose: The aim of the study was to assess physical and motor development of male students in relation to their place of permanent residence and monthly budget. Material and Methods: The research was conducted in 2012 and involved 361 male students. Physical development was assessed on the basis of the students' body mass and height as well as their BMI. In order to determine the level of motor development, 13 motor tests were applied. Results: It was stated that neither the students' body mass nor their BMI was significantly differentiated by their place of permanent residence or their monthly budget. In the vast majority of motor tests no relationship was observed between the students’ results and the place of permanent residence. Monthly budget was observed to significantly differentiate the level of motor fitness in the majority of motor tests. Conclusions: The students’ monthly budget more significantly than their place of permanent residence affects the students’ physical activity, and in consequence, their motor fitness.